Kuwait : 2020 Article IV Consultation-Press Release; Staff Report; and Staff Supplement. (IMF Staff Country Reports; Country Report, 2020)
This 2020 Article IV Consultation with Kuwait highlights that non-oil growth strengthened to estimated 3 percent in 2019, propelled by government and consumer spending. The challenge to reduce dependence on oil and boost savings has become more urgent. The subdued forecast for oil revenues is weighing on near-term growth and fiscal and external balances. Embedding fiscal measures in a comprehensive reform package that promotes private sector growth, strengthens governance and accountability, and improves public services would help build broad support for reforms. A rules-based fiscal framework would improve management of oil revenues. A rule-based framework would help anchor fiscal policy on a long-term objective of intergenerational equity. It should include a well-calibrated operational rule that helps reconcile long-term savings and near-term economic stabilization objectives. Financial sector reforms should focus on bolstering resilience and deepening inclusion. Sustaining reforms to foster private sector-led and diversified growth will be critical. With limited scope for public employment going forward, a vibrant private sector must emerge to absorb the large number of Kuwaitis entering the labor market in coming years.